Influences of Anlotinib on Cytochrome P450 Enzymes in Rats Using a Cocktail Method. (26th December 2017) - Sun, Wei; Wang, Zhe; Chen, Ruimin; Huang, Chengke; Sun, Rui; Hu, Xiaoxia; Li, Wanshu; Chen, Ruijie
Abstract : The present study aimed to investigate the effect of anlotinib (AL3818) on pharmacokinetics of cytochrome P450 (CYP) enzymes (CYP1A2, CYP2C6, CYP2D1, CYP2D2, and CYP3A1/2) by using five cocktail probe drugs in vivo. After pretreatment for 7 days with anlotinib (treatment group) or saline (control group) by oral administration, probe drugs phenacetin, tolbutamide, omeprazole, metoprolol, and midazolam were administered to rats by oral administration. Blood samples were obtained at a series of time-points and the concentrations of five probe drugs in plasma were determined by a UHPLC-MS/MS method. The results showed that treatment with anlotinib had no significant effect on rat CYP1A2, CYP2D2, and CYP2C6. However, anlotinib had a significant inductive effect on CYP2D1 and CYP3A1/2. Therefore, caution is needed during the concomitant use of anlotinib with other drugs metabolized by CYP2D1 and CYP3A1/2 because of potential drug-anlotinib interactions.